Answer:
(-6, 4)
Explanation:
We are given the following two equations and we are to solve them:
--- (1)
--- (2)
Using the substitution method:
From equation (2):
![3 x = 6 - 6 y \\\\ x = \frac { 6 - 6 y } { 3 } \\ \\ x = 2 - 2 y](https://img.qammunity.org/2020/formulas/mathematics/middle-school/pcfgy9n0ka3gkc7vos296jod3jxh0pj6z3.png)
Substituting this value of x in equation (1) to get:
![5 ( 2 - 2 y ) + 4 y = -14 \\\\ 10 - 10 y + 4 y = -14 \\\\ 1 0 + 14 = 6 y \\\\ y = \frac { 24 } { 6 } \\ \\ y = 4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/9yih229bylz4b21k82z23s4zixz25a6v0d.png)
Putting this value of y in equation (2) to find the value of x:
![3 x + 6 ( 4 ) = 6 \\\\ 3x + 24 = 6 \\\\ 3x = 6 - 24 \\\\ x = \frac { -18 } { 3 } \\\\ x = -6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/xusrk0ck5gx8hac9ts4l6vsgq96kl019nc.png)
Therefore, (-6, 4) is the solution to the given system of equations.